PARENTAL SEPARATION AND ITS EFFECTS ON STDUENT EDUCATION ACHIEVEMENT - PAWAN KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
There is a correlation between the dissolution of the relationship between a child’s parents and a slowed rate of intellectual development as well as worse academic accomplishment. It should not come as a surprise that the divorce or separation of a child’s parents can have a detrimental impact on the child’s motivation, engagement, and behaviour in the classroom that is related to learning. It should not come as a surprise that parental separation has been reported to have this effect because parental separation can result in a multitude of negative effects, including perceived guilt, blame, stressors, and diminished resources for the children. It has been reported to have this effect because parental separation has this effect. Although a number of studies have been carried out to investigate whether or not there is a correlation between the age at which a child’s parents divorce and their level of academic success, the results of these studies have been equivocal.